THE USE OF AUTHENTIC CARTOONS IN TEACHING ENGLISH LANGUAGE TO YOUNG LEARNERS - Sharipova, G.; Seitova, M. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
This article explains the importance of teaching English language to young learners by methods of using authentic cartoons. It’s important to create a real situation in the process of language learning. The solution to this problem we see in using authentic materials especially cartoons for young learners. The purpose of the article is identifying methods and techniques for rational introduction of authentic cartoons in the classroom for schoolchildren. The article discusses modern methods of teaching English, the most effective cartoons for listening and problems of using authentic cartoon based on the analysis of views of researchers to the problem of authentic materials.
Keywords: Teaching learning; methods; authentic cartoons; teaching materials